MEMBANGUN IDENTITAS PROFESIONAL: REFLEKSI DARI PROGRAM KAMPUS MENGAJAR - Sagala, Deni Roulina; Evi Karlina Ambarwati (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2025)
The development of a teacher's professional identity is important in the world of education but is often faced with challenges between theory and practice, especially for pre-service English teachers in Indonesia. This gap in understanding the profession's complexity can impact pre-service teachers' professional readiness and commitment. This study explores the influence of teaching mentoring experiences through the Kampus Mengajar Program on pre-service English teachers' professional identity formation. By employing a qualitative phenomenological approach, this study focuses on the reflections of a fifth-semester English Education Department student who participated in the program in 2023. Data were collected through reflective journals and semi-structured interviews and then analyzed using thematic analysis. The findings showed significant changes in pre-service teachers' views of the profession, improved pedagogical competence, and the formation of a stronger professional identity through self-reflection. The conclusion of this study emphasizes that field experience and deep reflection play an important role in building the professional identity of pre-service teachers who are ready to face the world of education.